Analisis Dampak Wewenang Polisi Dalam Penegakan Hukum di Indonesia - Putri, Kania Annisa; Nurfath, Al Fachri; Amelinda, Thalia; Nabila, Milani; Supriyadi, Tugimin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research analyzes the impact of police authority in law enforcement in Indonesia, which includes positive and negative aspects as well as implications for security and social justice. The police's broad powers play an important role in maintaining order and security, but also have the potential to give rise to abuse of power and human rights violations. Research methods include literature reviews, secondary data analysis, and case studies to identify and evaluate the impact of police policies and actions. The research results show that police authority contributes to reducing crime rates and increasing the sense of security in society. However, there are serious challenges such as abuse of authority, brutality, discrimination and lack of transparency that reduce public trust in the police. This research underlines the importance of structural and legal reform within the police, increasing supervision and accountability, as well as legal education for the community. Suggestions include the creation of an independent monitoring agency, the development of an effective complaints system, and increased interaction between the police and the community through collaborative programs. With these steps, it is hoped that law enforcement in Indonesia can run more effectively, fairly and transparently, thereby increasing public trust in police institutions.